2004
DOI: 10.1016/j.yexcr.2003.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α4β1 involvement in stromal cell-derived factor-1α-promoted myeloma cell transendothelial migration and adhesion: role of cAMP and the actin cytoskeleton in adhesion

Abstract: The chemokine stromal cell-derived factor-1alpha (SDF-1alpha) is expressed by bone marrow (BM) stromal cells and plays key roles in cell homing to and retention into the bone marrow. In multiple myeloma, blood-borne malignant plasma cells home to the BM and accumulate in contact with stromal cells, implicating myeloma cell migration across endothelium. Myeloma cells express the SDF-1alpha receptor CXCR4, as well as the integrin alpha4beta1, which mediates their attachment to BM stroma. We show here that SDF-1a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…CXCL12 is involved in several aspects of MM pathogenesis, including transendothelial migration, bone marrow retention of plasma cells, angiogenesis and osteoclastic bone resorption. [6][7][8][9][10][11] Based on previous studies showing that hypoxia regulates CXCL12 expression in other cell systems, [22][23][24][25][26] we examined the role of hypoxia in inducing aberrant CXCL12 expression in MM plasma cells. Given the limited number of primary MM plasma cells that can be recovered from MM patients and the difficulty associated with their in vitro culture, MM plasma cell lines were used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL12 is involved in several aspects of MM pathogenesis, including transendothelial migration, bone marrow retention of plasma cells, angiogenesis and osteoclastic bone resorption. [6][7][8][9][10][11] Based on previous studies showing that hypoxia regulates CXCL12 expression in other cell systems, [22][23][24][25][26] we examined the role of hypoxia in inducing aberrant CXCL12 expression in MM plasma cells. Given the limited number of primary MM plasma cells that can be recovered from MM patients and the difficulty associated with their in vitro culture, MM plasma cell lines were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] CXCL12 is highly expressed by MM plasma cells, 6 and circulating levels of CXCL12 are higher in the peripheral blood of MM patients than in age-matched normal donors and MGUS patients. 6,7 CXCL12 is an important mediator of several aspects of MM biology including transendothelial migration, 8,9 MM plasma cell migration and retention within the bone marrow, 10,11 angiogenesis, 7 and osteoclastic bone resorption. 6 Recent animal studies involving systemic injection of labeled MM plasma cells have also demonstrated that blocking the CXCL12/CXCR4 axis leads to a 20% reduction in bone marrow tumor burden.…”
Section: Introductionmentioning
confidence: 99%
“…This chemokine plays a major role in homing, because MM cells express the SDF-1α receptor, CXCR4 (Figure 3). Once in the BM, integrin α 4 B 1 (VLA-4) mediates attachment of MM cells to the stroma [58], and this process confers the cells a survival advantage. Adhesion of MM cells to fibronectin (FN) is known to protect the cells from druginduced apoptosis [23].…”
Section: Growth and Survival Factors Prevent Apoptosismentioning
confidence: 99%
“…Our study confirmed strong expression of CXCR4 on MM plasma cells but suggested reduced expression by SP plasma cells, which may make them chemotactically less susceptible to SDF-1. Binding of CXCR4 to SDF-1 is also thought to transiently upregulate a4b1 (VLA-4) surface expression (Sanz-Rodriguez et al, 2001;Parmo-Cabanas et al, 2004). The lack of this interaction in SP plasma cells may contribute to the reduced expression of a4 demonstrated here.…”
mentioning
confidence: 78%